Catch and kill : lies, spies, and a conspiracy to protect predators - Farrow, Ronan, 1987- (New York : Little, Brown and Company, 2019)
This is the untold story of the exotic tactics of surveillance and intimidation deployed by wealthy and connected men to threaten journalists, evade accountability, and silence victims of abuse. And it's the story of the women who risked everything to expose the truth and spark a global movement.
Prologue -- Part I: Poison Valley. Tape ; Bite ; Dirt ; Button ; Kandahar ; Continental ; Phantoms ; Gun ; Minions ; Mama ; Bloom ; Funny ; Dick -- Part II: White whale. Rookie ; Static ; F.O.H. ; 666 ; Quidditch ; Spiral ; Cult ; Scandal ; Pathfinder ; Candy ; Pause ; Pundit ; Boy ; Altar ; Pavonine -- Part III: Army of spies. Fakakta ; Bottle ; Syzygy ; Hurricane ; Goose ; Letter ; Mimic ; Hunter ; Heist ; Celebrity ; Fallout ; Dinosaur ; Mean -- Part IV: Sleeper. Edify ; Cabal ; Charger ; Nightgown ; Pretexting ; Running ; Gaslight ; Vacuum ; Playmate ; Chupacabra -- Part V: Severance. Circle ; Axiom ; Pegasus ; Melting ; Zdorovie ; Spike ; Launder ; Blacklist -- Epilogue.
Includes bibliographical references (pages 420-441) and index.
Keywords: Farrow, Ronan, -- 1987-; Weinstein, Harvey, -- 1952-; Lauer, Matt, -- 1957-; Investigative reporting -- United States; Intimidation; Espionage; Women -- Crimes against -- United States; Sexual abuse victims -- United States; Sexual harassment -- Investigation -- United States; Rape -- Investigation -- United States; Sex crimes -- Investigation -- United States; Los Angeles (Calif.) -- Social conditions; Hollywood (Los Angeles, Calif.) -- Social conditions